The Challenges of Post-Modern Political Theory and Theorizing - Davies, Emmanuel Opuene (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
Post-modern theory and theorizing are as critical and fundamental as they are pungent in understanding, describing and analyzing political events, actions, activities and trends in societies. Essentially, the application of political theories as dependable frameworks or tools of analysis for studying and analyzing politics in contemporary times is fraught with a number of challenges. The major objective of this paper is to examine the challenges faced by Post-modern political theory and theorizing. This paper adopts the historical descriptive method of analysis. Much of the study is based on archival and library research which include texts, journals, models and works of other scholars related to the study. In an attempt to answer the question, what are the challenges plaguing Post-modern political theory and theorizing, the paper identified interpretation, consistency and language, critical appraisal and value-judgment, background influences and objectivity, among others as some of the challenges. The paper recommended, among others, that there should be consistency and uniformity in interpretation of theories, Political theorists should come to an agreement or consensus on the role and purpose of the state instead of having different views, there should be objectivity in political theory and theorizing. The paper concluded by strongly suggesting that the earlier the challenges are addressed the better the future of political theory and theorizing. Keywords: Post-Modern, Political Theory, Theorizing, Challenges.